Environmental impacts of aquifer thermal energy storage (ATES). (November 2021) - Stemmle, Ruben; Blum, Philipp; Schüppler, Simon; Fleuchaus, Paul; Limoges, Melissa; Bayer, Peter; Menberg, Kathrin
Abstract: Aquifer Thermal Energy Storage (ATES) is an open-loop geothermal system allowing long-term storage of thermal energy in groundwater. It is a promising technology for environmentally friendly energy generation that can reduce greenhouse gas (GHG) emissions. In the literature, there are few studies on the greenhouse gas emissions caused by ATES systems over their entire life cycle. Thus, this study presents a novel life cycle assessment (LCA) regression model that can be used for a wide range of ATES configurations due to its parametric structure. This model is a fast alternative to conventional time-consuming LCAs. Combined with a Monte Carlo simulation, it enables the analysis of the environmental impacts of a large variety of hypothetical ATES systems and therefore the evaluation of the technology as a whole. Compared to conventional heating systems based on heating oil and natural gas, the median value of the Monte Carlo simulation results in GHG savings of up to 74%. In comparison to cooling techniques using today's electricity mix, ATES can save up to about 59% of GHG emissions, while also being economically competitive. When considering a projected electricity mix for the year 2050, the GHG emission savings resulting from a second LCA regression model are as high as 97%. The findings of our sensitivity analysis show which ATES design parameters should be optimized when planning new systems. In particular, the most important design parameters operating time cooling and coefficient of performance (COP) of the heat pump should be carefully considered. Highlights: Novel life cycle regression model for aquifer thermal energy storage is developed. Greenhouse gas emission (GHG) savings of up to 74% are possible. Emission savings are even higher when using a renewable electricity mix. The most important design parameters are identified.